Beyond the guidelines management of juvenile idiopathic arthritis: a case report of a girl with polyarticular disease refractory to multiple treatment options and Leri Weill syndrome - Vana Vukić; Ana Smajo; Mandica Vidović; Rudolf Vukojević; Miroslav Harjaček; Lovro Lamot (BMC, 2021)
Abstract Background The last two decades brought new treatment options and high quality guidelines into the paediatric rheumatologic practice. Nevertheless, a number of patients still present a diagnostic and therapeutic challenge due to combination of vague symptoms and unresponsiveness to available treatment modalities. Case presentation We report a case of sixteen years old girl suffering from polyarticular type of juvenile idiopathic arthritis refractory to multiple treatment options. She first presented at the age of 4 with swelling and contractures of both knees. Her symptoms were initially unresponsive to nonsteroidal anti-inflammatory drugs and progressed despite treatment with intraarticular and systemic glucocorticoids and methotrexate. Throughout the years, she received several biologics together with continuous administration of nonsteroidal anti-inflammatory drugs and disease modifying anti-rheumatic drugs as well as intraarticular and systemic glucocorticoids in disease flares. However, none of this options  provided a permanent remission, so various other modalities, as well as other possible diagnoses were constantly being considered. Eventually she became dependent on a daily dose of systemic glucocorticoids. In 2018, the treatment with Janus kinase inhibitor tofacitinib was initiated, which led to gradual amelioration of musculoskeletal symptoms, improvement of inflammatory markers and overall well-being, as well as to the weaning of systemic glucocorticoids. As the swelling of the wrists subsided for the first time in many years, Madelung's deformity was noticed, first clinically, and later radiographically as well. Genetic analysis revealed short-stature homeobox gene deficiency and confirmed the diagnosis of Leri Weill syndrome. Conclusions This case report emphasizes the need for reporting refractory, complicated cases from everyday clinical practice in order to build-up the overall knowledge and share experience which is complementary to available guidelines. Individual reports of difficult to treat cases, especially when additional diagnoses are involved, can be helpful for physicians treating patients with common rheumatological diseases such as juvenile idiopathic arthritis.